1998
DOI: 10.1086/515006
|View full text |Cite
|
Sign up to set email alerts
|

Declining Rates of Oropharyngeal Candidiasis and Carriage ofCandida albicansAssociated with Trends Toward Reduced Rates of Carriage of Fluconazole‐ResistantC. albicansin Human Immunodeficiency Virus –Infected Patients

Abstract: In order to determine the current prevalence and incidence of fluconazole-resistant oropharyngeal candidiasis among human immunodeficiency virus (HIV)-infected patients, we conducted a prospective observational study of a consecutive series of HIV-infected patients. Of 128 enrolled patients, 70 patients completed four quarterly follow-up visits over a period of 1 year. Over this period, declining rates of carriage of Candida albicans (from 61% to 39%; P = .008) and of oropharyngeal candidiasis (from 30% to 4%;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 6 publications
4
52
0
2
Order By: Relevance
“…A similar improvement in fluconazole susceptibility among Candida albicans isolates from AIDS patients has been noted following the introduction of HAART (27). It was suggested that decreased use of antifungal agents in patients treated with effective antiretroviral therapy may have contributed to the decrease in fluconazole-resistant strains colonizing and infecting these individuals (27).…”
Section: Resultsmentioning
confidence: 74%
“…A similar improvement in fluconazole susceptibility among Candida albicans isolates from AIDS patients has been noted following the introduction of HAART (27). It was suggested that decreased use of antifungal agents in patients treated with effective antiretroviral therapy may have contributed to the decrease in fluconazole-resistant strains colonizing and infecting these individuals (27).…”
Section: Resultsmentioning
confidence: 74%
“…Although the incidence of OPC in HIV infection has been significantly reduced since the introduction of highly active antiretroviral therapy (HAART) (2), it remains a common opportunistic infection in HIV-infected patients worldwide.…”
Section: S Tudies Report Oropharyngeal Candidiasis (Opc)mentioning
confidence: 99%
“…Antifungal resistance to fluconazole (FCZ), itraconazole (ITZ), and ketoconazole (KTZ) has been described and particularly in the setting of oral candidiasis in HIV/AIDS patients (6,14,15,25,26). Cross-sectional surveys have indicated a prevalence of FCZ-resistant oral C. albicans isolates of 12 to 19% (20).…”
mentioning
confidence: 99%
“…Cross-sectional surveys have indicated a prevalence of FCZ-resistant oral C. albicans isolates of 12 to 19% (20). Before the use of HAART, Martins et al (14,15) found a prevalence of Candida spp. resistant to FCZ of 22% in North Americans with oral candidiasis and of 14% in asymptomatically colonized patients.…”
mentioning
confidence: 99%